2008
DOI: 10.5507/bp.2008.016
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Estradiole and Tibolone Administration on Leptin Levels in Women With Surgically Induced Menopause

Abstract: Background: Several studies suggest that changes in estrogens and androgens during menopause play a role in the regulation of leptin production. Some authors present hypothesis that sex hormone replacement therapy can modulate leptin levels but up to date evidence shows that the infl uence of endogenous estrogens, androgens levels and sex hormone therapy on leptin concentration remains uncertain.Aim: To evaluate the infl uence of surgically induced menopause on serum leptin levels and the infl uence of diff er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They also found that leptin levels were elevated after six months of HT in 45 women (P < 0.001). However, studies led by Petzel, 33 Nar, 34 and Lambrinoudaki, 26 found no significant effect of HT on serum leptin levels.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…They also found that leptin levels were elevated after six months of HT in 45 women (P < 0.001). However, studies led by Petzel, 33 Nar, 34 and Lambrinoudaki, 26 found no significant effect of HT on serum leptin levels.…”
Section: Resultsmentioning
confidence: 97%
“…Of note, none of the 6 studies of at least 1-year duration demonstrated increases in leptin levels in HT-treated groups, although leptin levels rose in untreated women in 4 of the studies. Finally, some studies described findings on selective estrogen receptor agents 26,28,33,37,38,40 whose effects on serum leptin levels and body weight are poorly understood.…”
Section: Discussionmentioning
confidence: 99%